2018
DOI: 10.1016/j.mcn.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

d-Serine administration affects nitric oxide synthase 1 adaptor protein and DISC1 expression in sex-specific manner

Abstract: Antipsychotic medications are inefficient at treating symptoms of schizophrenia (SCZ), and N-methyl d-aspartate receptor (NMDAR) agonists are potential therapeutic alternatives. As such, these agonists may act on different pathways and proteins altered in the brains of patients with SCZ than do antipsychotic medications. Here, we investigate the effects of administration of the antipsychotic haloperidol and NMDAR agonist d-serine on function and expression of three proteins that play significant roles in SCZ: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…Cortices were dissected from embryonic rat brains at gestational day 18 as previously described 36 , 37 and in accordance with protocols approved by the Rutgers Animal Care and Facilities Committee and the National Institutes of Health guide for the care and use of Laboratory animals (Rutgers Institutional AAALAC Accreditation Number: 000534). Tissue was triturated, and neurons were dissociated and cultured.…”
Section: Methodsmentioning
confidence: 99%
“…Cortices were dissected from embryonic rat brains at gestational day 18 as previously described 36 , 37 and in accordance with protocols approved by the Rutgers Animal Care and Facilities Committee and the National Institutes of Health guide for the care and use of Laboratory animals (Rutgers Institutional AAALAC Accreditation Number: 000534). Tissue was triturated, and neurons were dissociated and cultured.…”
Section: Methodsmentioning
confidence: 99%
“…Svane etal. (55) administered D-serine to male and female rats and measured expression of nitric oxide synthase1 adaptor protein (NOS1AP) (overexpressed in cortex of patients with schizophrenia), D2 receptors and DISC1 and found that it affects expression of these three genes in a sex-specific manner. Mustafa etal.…”
Section: Formation and Catabolism Of D-serine And Relevance Of This Mmentioning
confidence: 99%
“…For example, recall when NOS1AP is overexpressed, dendritic arborization decreases (Wang et al., 2016). However, activation of NMDAR with the agonist d ‐serine has been found to decrease the expression of NOS1AP in male but not in female rats, restoring the dendritic branching that NOS1AP inhibits in rat cortical neurons (Svane et al., 2018). This study provides evidence that sex differences in NO signaling via the nNOS binding partner, NOS1AP, may underlie some of the sex differences seen in dendritic patterning of developing neurons.…”
Section: Discussionmentioning
confidence: 99%